2012
DOI: 10.2119/molmed.2011.00428
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-33 Ameliorates Experimental Colitis through Promoting Th2/Foxp3+ Regulatory T-Cell Responses in Mice

Abstract: Crohn's disease (CD) is characterized by the activation of Th1 and Th17 cells and deficiency of regulatory T cells (Tregs), leading to intestine tissue injury and destruction. As a novel cytokine of the interleukin (IL)-1 family, the role and underlying mechanisms of IL-33 in CD remain poorly understood. Here, we assess the effects and mechanisms of IL-33 on the trinitrobenzene sulfonic acid (TNBS)-induced experimental colitis that mimics human CD. We found that IL-33 levels were increased in the TNBS-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
132
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(150 citation statements)
references
References 48 publications
10
132
0
1
Order By: Relevance
“…Finally, the IL-33 treatment regimen provided functional benefit alleviating the sensorimotor deficits induced by pMCAo. Our data are in line with previously reported beneficial function of IL-33 in a mouse model of SCI (Pomeshchik et al, 2014), EAE (Duan et al, 2012) and atherosclerosis (Miller et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Finally, the IL-33 treatment regimen provided functional benefit alleviating the sensorimotor deficits induced by pMCAo. Our data are in line with previously reported beneficial function of IL-33 in a mouse model of SCI (Pomeshchik et al, 2014), EAE (Duan et al, 2012) and atherosclerosis (Miller et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Since Tregs were shown to mediate the protective effects of IL-33 in EAE (Duan et al, 2012) and the lack of IL-33 signaling reduced the amount of Tregs in atherosclerotic mice (Wasserman et al, 2012), Tregs were potential candidates for mediating the IL-33-induced protection. To our surprise, depletion of Tregs failed to prevent IL-33 induced protection after pMCAO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this study, St2 is also identified as one of the top differentially unregulated genes in colonic Treg cells [26]. There are several published reports showing that administration of recombinant IL-33 led to a significant increase in the frequency and total number of splenic Treg cells [25,26,49,51]. However, Treg induction by IL-33 is TGF-␤1 dependent, as addition of IL-33 to iTreg cultures significantly increases both the percentage and total number of Foxp3-expressing cells but has no effect on Foxp3 expression in the absence of TGF-␤1 [26].…”
Section: Il-33/st2l In Treg Cellssupporting
confidence: 87%
“…A large number of evidences have supported its pathogenic role in arthritis [21], asthma [22], colitis [23], and acute kidney injury [24]. However, protective role for IL-33 has also been described in murine models of acute colitis [25,26], experimental autoimmune uveitis [27] and chronic cardiac rejection model [28].…”
Section: Introductionmentioning
confidence: 99%